The Female Circumcision Controversy : An Anthropological Perspective - Gruenbaum, Ellen (Book collections on Project MUSE., 2001)
Ellen Gruenbaum looks at the validity of Western arguments against the practice of female circumcision. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions--in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.